Silver Nanoparticles Biosynthesized Using Azadirachta indica Fruit and Leaf Extracts: Optimization, Characterization, and Anticancer Activity - Alharbi, Njud S.; Alsubhi, Nehad S. (Journal of Nanomaterials, 2023)
Silver nanoparticles (AgNPs) are becoming increasingly important for various crucial applications, including antimicrobial, anticancer, catalytic, and anti-inflammatory. AgNPs biosynthesized from plant extracts have attracted considerable attention because of their eco-friendliness, simplicity, cost-effectiveness, and stability. This study investigated the potential of using fruit and leaf extracts of the medicinal plant Azadirachta indica as a capping and reducing agent for the biosynthesis of AgNPs. The size, shape, and optical properties of AgNPs significantly affect their chemical, physical, and biological activity. Therefore, this study optimized the biosynthesis conditions as a first attempt for A. indica fruit extracts to produce AgNPs with precise morphology. Subsequently, the biologically manufactured AgNPs were characterized using suitable techniques. Their potential anticancer activities were examined against in vitro human lung and breast cancer (H1975 and MCF-7) cell lines. The AgNPs were stable, with a high yield and a spherical shape, ranging in size from 14 to 19 nm and exhibiting an absorption band between 420 and 440 nm. The AgNPs biosynthesized using A. indica fruit and leaf extracts were shown to be highly toxic against in vitro H1975, with IC50 of 62.2 and 91 µg/mL, respectively. The IC50 values were 67.5 and 68.7 µg/mL when testing against the MCF-7 cells. These findings suggest that plant-derived nanoparticles have enormous potential for future biomedical applications, which warrants further investigation.